Comparative analysis of cranberry fruit rot fungal diversity in Massachusetts from wild, organic, and conventional ecosystems using multiplex PCR - Sulley, Salisu; Devi, Mura Jyostna; Cinget, Benjamin; Conti, Matteo; Bélanger, Richard; Sylvia, Marty; Caruso, Frank; Uppala, Leela Saisree (Frontiers in Plant Science, 2025)
Cranberry fruit rot (CFR) has been a major challenge in cranberry production affecting fruit quality, particularly in Massachusetts and New Jersey. It is known to be a disease complex associated with several diverse fungi. This study provides the first comprehensive assessment of CFR fungal population dynamics across wild, organic, and conventional cranberry production systems in southeastern Massachusetts. By employing multiplex PCR, a high-throughput molecular method for the simultaneous detection of multiple fungi, we investigated the prevalence and diversity of 11 most commonly associated fruit rot fungi in 2021 and 2022, in 32 (23 conventional, 4 organic and 5 wild) and 50 (40 conventional, 4 organic and 6 wild) cranberry bogs respectively. Significant differences in the detection of CFR fungi were observed across these ecosystems. Conventional fields showed varied fruit rot incidence, ranging from 2-42% in 2021 and 1-48% in 2022. Species richness analysis indicated that on average, wild bogs were more species-rich and diverse, with 5.5 CFR fungi detected per sample compared to 4 CFR fungi in both conventional and organic bogs. Organic bogs exhibited a significant decline in species richness from 6 fungi in 2021 to 2 fungi in 2022. Except for Phomopsis vaccinii, which was not observed in organic bogs in either year, all 11 CFR fungi were detected across the ecosystems: some in both growing seasons and some in only one. Key CFR fungi such as Coleophoma empetri, Allantophomopsis cytisporea and Botryosphaeria vaccinii were consistently found across all ecosystems and both years of study. Analysis of year-to-year variation indicates that wild bogs exhibited higher fungal carryover, with 8 out of the 11 CFR fungi persisting from one year to the next, compared to 6 fungi in conventional bogs and 4 fungi in organic bogs. Notably, C. empetri, B. vaccinii, and A. cytisporea demonstrated year-to-year persistence across all three bog types. Among these, C. empetri exhibited the greatest persistence across all three ecosystems, with 96%, 100% and 60% of the conventional, organic and wild bogs maintaining its presence across both years. Colletotrichum spp. persisted in 43% of the conventional bogs but detected only in one of the two years studied in organic and wild bogs resulting in 0% persistence from one year to the next. The study also noted a general decrease in Botryosphaeria vaccinii and an increase in Physalospora vaccinii across all bog types. This research highlights the varying persistence and complex dynamics of CFR fungi across different cranberry ecosystems, as well as the potential impact of management practices on fungal populations.